2012
DOI: 10.3895/s1981-36862012000100012
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização De Variedades De Batata Do Municipio De Contenda-Pr E Indicações Quanto Ao Uso Doméstico E Tecnológico

Abstract: A batata, Solanum tuberosum L, nativa dos Andes, da região do Peru e Colômbia, já era consumida há 8000 anos. Tubérculo rico em carboidratos, a batata apresenta duas vezes mais proteínas que a mandioca, além de vitaminas e sais minerais. O brasileiro consome aproximadamente 13 kg/ano, enquanto a média de consumo de europeus e americanos é cinco vezes maior. Estes dados indicam o grande potencial de aumento de consumo de batata no Brasil. O Município de Contenda tem sido um dos maiores produtores de batata no e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2013
2013
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
1
0
0
1
Order By: Relevance
“…The present study revealed that the PDA medium is a general medium for growth due to its nutritional value, which is in agreement with (Trindade, 1994). A similar result was obtained by (Palacios-Cabrera et al, 2005) they found that the A. niger was able to grow in all culture media, Czapeck Yeast extract Agar (GYA), Dichloran 18% Glycerol Agar and Malt Yeast extract 40% Glucose Agar (MY40G).…”
Section: Discussionsupporting
confidence: 77%
“…The present study revealed that the PDA medium is a general medium for growth due to its nutritional value, which is in agreement with (Trindade, 1994). A similar result was obtained by (Palacios-Cabrera et al, 2005) they found that the A. niger was able to grow in all culture media, Czapeck Yeast extract Agar (GYA), Dichloran 18% Glycerol Agar and Malt Yeast extract 40% Glucose Agar (MY40G).…”
Section: Discussionsupporting
confidence: 77%
“…Fernandes et al (2010) também observaram menores teores de cinzas na cultivar Ágata (0,79%), entre as cultivares testadas. Trindade (1994) Os teores de proteína são afetados pela adubação e manejo da cultura LACHMAN et al, 2005). Cem gramas de batata suprem cerca de 10% das necessidades de um adulto em tiamina, niacina, vitamina B6 e ácido fólico; 50% da vitamina C e 10% da demanda de proteínas (PEREIRA; LUZ; MOURA, 2005).…”
Section: Resultsunclassified